# Math Homework Help

### Showing All Questions Answered Popular Recommended Unanswered Editor's Choice in Math

• Math
Given the equation: x^3+ x^2 + x +1 = 0 We need to find x values that satisfies the equation. First we will simplify by factoring. We will factor x^2 from the first two terms. ==> x^2 ( x+1) +...

Asked by kokibrazil on via web

• Math
Given the volume of the cylinder is v= 234 The height = 12 We need to find the surface area. First we will need to find the radius. We know that the volume if given by : v= r^2*pi*h where r is the...

Asked by yasmin130 on via web

• Math
Let x be the number of people attends. Let the revenue be y. Let the initial revenue when 120 people attend is 30*120 = 3600 y= people attend * price y= (120+x)*(30- 1.5*(x/10)] y= (120+x) * ( 30...

Asked by rosemin on via web

• Math
The system is consisted of 4 variables and 4 equations as follow: Let the variables be x,y,z, and u ==> 6x +2y -z -5u = -25 ==> -x +7z +3u = 7 ==> x -y -10z +6u = 23 ==> 8y + z -11u = -21

Asked by richie4321 on via web

• Math
f(x) = 8x +4 Given that f(a) = 1.6 We need to find the values of a. We will substitute with x= a into the function f(x). ==> f(a) = 8a +4 = 1.6 Now we will solve for a. ==> 8a = 1.6 -4 =...

Asked by enotes on via web

• Math
Given the formula: V = C(1-r)^t v is the values c is the original cost = 40,000 r is the rate = 8% = 0.08 t is the number of years Given the information above, we need to find t such that v=...

Asked by swavers on via web

• Math
Given f(x) = 6x+4 We need to find the values of a such that f(a) = -1.3 We will substitute with x=a into the equation. ==> f(a) = 6a +4 But given that f(a) = -1.3 ==> f(a) = 6a+4 = -1.3 Now...

Asked by colege on via web

• Math
A=P (1+r)^t A = Value of CD P = original amount= 1000 r = the rate = 3% = 0.03 t= time We need to find t such that A is doubled ==> A = 2*1000 = 2000 Now we will substitute. ==> 2000 =...

Asked by sammysoso on via web

• Math
We have to simplify (e^x - e^-x)^7 (e^x - e^-x)^7 => (e^x - 1/(e^x))^7 => [(e^x * e^x - 1)/(e^x)]^7 => (e^x * e^x - 1)^7/(e^x)^7 => (e^2x - 1)^7 / e^7x We could expand the numerator...

Asked by doni2633 on via web

• Math
First, we'll move all the powers of 7 to the right side of the equal sign. 2^x + 2^(x+1) + 2^(x+2) = 7^x + 7^(x+1)+7^(x+2) Now, we'll apply the property of exponentials: a^(b+c) = a^b*a^c According...

Asked by n1kaa on via web

• Math
We'll expand the binomial and we'll get: (1+x)^6 = a0 + a1*x + a2*x^2 + ... + a6*x^6 a0,a1,a2,...,a6 are the coefficients of polynomial. The sum of even coefficients is: a0 + a2 + a4 + a6 We know...

Asked by iszabelle on via web

• Math
Since a1,a2,...,an are the terms of an A.P., we'll apply the rule of finding each term of the arithmetical sequence: a2 = a1 + d => a2 -a1 = d a3 = a1 + 2d => a3 - a1 = 2d...

• Math
Well re-write 4^(2x+1) = 4^2x*4 and 6^(x+2) = 6^x*6^2 We'll re-write the entire expression: 3^x*4^2x*4 = 6^x*6^2 We'll write 6^x = 2^x*3^x 3^x*4^2x*4 = 2^x*3^x*36 We'll divide by 4*3^x: 4^2x =...

Asked by ljsarg on via web

• Math
The formula for the surface area of the cone is the following: SA = area of the base + area of the cone. Area of the base = r^2 * pi Area of the cone = r*s*pi ( r is the radius of the base and s...

Asked by tanaya98 on via web

• Math
Only values of a which are greater than or equal to 0 will make the expression inside the absolute symbol (that is -a) negative. Therefore, for the property |-a| = a to be meaningful, a must be...

Asked by katlego1 on via web

• Math
You have to remember that the number of solutions of an equation is equal to the highest power of the variable. A linear variable has 1 solution; a quadratic equation has 2 solutions, etc. The...

Asked by chezmena on via web

• Math
When the tire rotates 400 r/ m , then the distance the tire travels in one minute = 400 * circumference of the tire for 1 minute ==> D = 400 * C...............(1) Now we will calculate the...

Asked by eino1 on via web

• Math
You want the value of x for which sin x - cos x = 0. Why are you taking the cases where cos x = 1, sin x = 0, etc. Instead, solve for x. sin x - cos x = 0 => sin x = cos x => sin x / cos x =...

Asked by nena1993 on via web

• Math
You have to solve x = sin x If you have a look at the graph of the sine function you see that it starts from the point (0,0). At this point the value of the sin function is zero and the value of x...

Asked by bulbul on via web

• Math
We have the functions: f(x)=|x|, g(x)=6x-8 and h(x) = 4-x. We have to find u= fo(gof)/h. u = fo(gof)/h => u = fo[(g(f(x))/ h(x)] => u = fo[(6|x| - 8) / (4 - x)] => u = |(6|x| - 8)|/ |(4 -...

Asked by penarul on via web

• Math
The equation 2*lg(x-1) = lg (ax-3) has two equal roots. 2*lg(x-1) = lg (ax-3) => lg ( x-1)^2 = lg (ax - 3) taking the antilog of both the sides => (x - 1)^2 = ax - 3 => x^2 - 2x + 1 = ax -...

• Math
The equation of the line between the points (6, 3) and (3, 4) is y – 3 = (x – 6)[(4 – 3)/(3 – 6)] => y – 3 = (x – 6)*( -1/3) The slope of the line is (-1/3). The equation of the line...

Asked by xetaalpha on via web

• Math
Law 1: log x + log y = log (x*y) Example: log 2 + log 5 = log (2*5) = log 10 = 1 Law 2: log x - log y = log x/y Example: log 100 - log 10 = log 100/10 = log 10 = 1 Law 3: log x^a = a* log x...

Asked by maleeha2882 on via web

• Math
The slope of the tangent to a curve f(x) is the value of the first derivative of the curve for the appropriate x. Here we have x^2 + y^2 = 34 Differentiating both the sides 2x + 2y (dy/dx) = 0...

Asked by fish-swim on via web

• Math
We'll substitute x by 2 and we'll get: lim (lnx-ln2)/(x-2 x) = lim (ln 2 - ln 2)/(2 - 4) lim (lnx-ln2)/(x-2 x) = 0/-2 =0 But this is the value of the limit of the function, if and only if the...

• Math
We have to prove that (1+2(sin a)(cos a))/(1-2(sin^2 a)=(cos a+sin a)/(cos a-sin a) Starting from the left hand side (1+2(sin a)(cos a))/(1-2(sin a)^2) replace 1 with (sin a)^2 + (cos a)^2 =>...

Asked by fuc113190 on via web

• Math
Let's denote the number of students as S. 5/7 of them are boys. If we denote the number of boys as B, B = (5/7)*S The rest of the students are girls. This is equal to (1 - 5/7)*S = (2/7)*S As the...

Asked by maureenwood on via web

• Math
ln t = - ln 2 We will preview the properties of the logarithm equations. We know that: ln a^b = b*ln a Then we will rewrite the equation. - ln 2 = -1 * ln 2 = ln 2^-1 = ln (1/2) ==> ln t = ln...

Asked by colorcolour on via web

• Math
x^2 + 6x + 6 = -3 + (x+3)^2 To prove, we will start form the left side and prove the right sides. First we will complete the square. ==> (x^2 + 6x +6) We will add and subtract( x's...

Asked by happybee on via web

• Math
We have to prove that 3+1/(x+1) has a unique solution. 3+1/(x+1) => [3(x +1) + 1] / (x+1) => [3x + 3 + 1] / (x +1) => [3x + 4] / (x + 1) We see that the maximum power of x in the function...

Asked by lexijuly on via web

• Math
We have to solve the inequation x/2 >= 1 + 4/x x/2 >= 1 + 4/x => x >= 2 + 8/x If we assume that x >=0, we can multiply both the sides of the inequation with x without changing the...

Asked by katlego on via web

• Math
To calculate cosine, using adjacent dided by hypotenuse. Tangent is opposite over adjacent. opposite =10 adjacent = 24 So you are missing hypotenuse. In a right triangle, c is the hypotenuse....

Asked by cartoffried on via web

• Math
The answer to this question is that the Arctic Wolf is 40 kg. and the bobcat is 8 kg. You can set up the equation as 1/5 X + X =48kg. Next, multiply 1/5 X by 5 to make it a whole number, or X....

Asked by opopopopoq on via web

• Math
We have the function f(x) = sqrt x + a. At x= 16, the tangent to to the function is y = mx + 2 The slope of the tangent to the function f(x) = sqrt x + a at x = 16 is m. f'(x) = (1/2)/ sqrt x =>...

Asked by tafy222 on via web

• Math
We have f(x) = (x + 8)^2. We have to find the equation of the tangent to the graph at the point where x = -2. The slope of the tangent drawn to a graph f(x) at the point (x, f(x)) is the value of...

Asked by enotes on via web

• Math
We'll start using the condition from enunciation that the binomial coefficients of the given expansion are in arithmetical progression. Since it is not indicated what are the terms, we'll suppose...

Asked by pavelpimen on via web

• Math
We have to prove: sin^4(theta) - cos^4(theta) = sin^2(theta) - cos^2(theta) First let's write the terms in a standard form and use x instead of theta. So we have to prove (sin x)^4 - (cos x)^4 =...

Asked by fish-swim on via web

• Math
We have the length of the sides of the triangle given as 4 ,5 and 8. Let us denote the sides as a = 4, b = 5 and c= 8. The angles A, B and C are opposite the three sides. The angles of the...

Asked by schooldump on via web

• Math
The surface area of a cube of side s is given by 6*s^2 . Here the surface area is 486 m^2 6*s^2 = 486 => s^2 = 486 / 6 => s = sqrt 81 => s = 9 The diagonal length of a cube of side 9 is...

Asked by rogerwalt on via web

• Math
You have given that the card has an interest free period of 32 days. The man spends \$32000 using his card and pays back \$20000 within 32 days, the rest is paid after 45 days. He incurs an interest...

Asked by regheal1 on via web

• Math
The sides of the triangular park are of 80 m , 100 m and 120 m. The area of the park can be calculated using Heron’s formula which gives the area as sqrt [s*(s – a)(s – b)(s – c)] where a,...

Asked by rbeaker91 on via web

• Math
f(x) = (x-2)/(2x-3) To find the derivative, we will use the quotient rule. Let f(x) = u/v such that: u= x-2 ==> u' = 1 v= (2x-3) ==> v' = 2 Then we know that: f'(x) = [ u'*v - u*v']/ v^2...

Asked by clara2 on via web

• Math
Given the point (a,2) and the point (3a,-5). We need to find the distance in terms of a. We will use the distance between two points formula to calculate. ==> We know that : D = sqrt[ (x1-x2)^2...

Asked by jude69 on via web

• Math
Let the distance both cars travels before they meet is D. The time need to for car 1 is T1 The car needed for car 2 is T2 But car 2 leaves 30 minutes ( 0.5 h) after car 1 ==> T2 = T1 - 0.5...

Asked by nano75 on via web

• Math
2- 5*l 2x-3 l < 7 First we will need to isolate the absolute values on the left side. Let us subtract 2 from both sides. ==> -5*l2x-3l < 5 Now we will divide by -5 and reverse the...

Asked by feres on via web

• Math
Given the right angle triangle at B is ABC such that: AB = 6 BC= 7 Then the hypotenuse is AC Now we will calculate the length of the hypotenuse. ==> AC^2 = AB^2 + BC^2 ==> AC^2 = 6^2 + 7^2 =...

Asked by ryanomar on via web

• Math
Let the length of the rectangle be L and the width is W. Given that the length is twice the width. ==> L = 2*W ............(1) Also, given that the area of the rectangle is 98. ==> L*W = 98...

Asked by totoo on via web

• Math
We are given the equation of the line 2x-y+2 = 0 We will rewrite into the slope form. ==> y= 2x+2 ..........(1) Also, given the equation of the curve g(x) = x^2 -3x -7 We need to find the...

• Math
Given the curve p(x) = (x-2)(3x-1) We need to find the integral of p(x) between 0 and 1 First we will simplify and open the brackets. ==> p(x) = 3x^2 -x -6x +2 ==> p(x) = 3x^2 -7x +2 Now we...

Asked by lalooo on via web